PEMBERDAYAAN MASAYARAKAT MELALUI PELATIHAN DAN PEMANFAATAN MANGGA MENJADI ANEKA MACAM OLAHAN MAKANAN DI RW.09 KAMPUNG NANAS, KEL. TELUK TERING, KEC. BATAM KOTA, PROVINSI KEPULAUAN RIAU - Junianto, Pilifus; Nggala, Yuliana Kafenia Putri (Jurnal Pengabdian Bukit Pengharapan, 2023)
The aim of carrying out this community service activity is as a form of implementing collaboration between STIE Bentara Persada and the residents of RW.09 Kampung Nanas, Kel. Teluk Kering, Kec. Batam City in the form of training and utilization of mangoes into various processed foods. This program was held on Saturday, April 29 2023 with STIE Bentara Persada students and aims to help residents increase their family's economic value and become a source of employment opportunities for the local community. Overall, this activities received a positive enthusiastic response from residents.